Enhancing Photovoltaic Panel Efficiency Through Phase Change Material: An Experimental Investigation Under Diverse Weather Conditions - Badgujar, Sachin Prabhakar; Kumar, Cheruku Sandesh; Wagh, Dr. Hemant Krishnarao (Migration Letters, 2024)
In this study, we explore the integration of photovoltaic/thermal (PV/T) technology, a fusion of PV modules for photovoltaic utilization and a novel phase change material (PCM) utilization, aimed at enhancing the comprehensive efficiency of solar energy utilization, with promising applications. We introduce a direct expansion solar PV PCM, coupling PV modules with a PCM, specifically designed for improving performance. To address the need for stable and performing residential solar PV, we propose and simulate a solar PV system integrated with phase change material (PCM. Outcomes demonstrate that underfloor heating utilizing PCM can maintain temperatures between ranges after applying phase change material to PV panel. Additionally, we observe a decrease in the heating of solar panel which leads to increase in Performance. A 0.949 m2 PV panel module can contribute 21.07% of its electricity output to the power grid under a solar radiation intensity. These findings underscore the viability and efficiency gains of integrating PV technology with PCM.